2014
DOI: 10.1037/a0036496
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between working memory for serial order and numerical development: A longitudinal study.

Abstract: Despite numerous studies, the link between verbal working memory (WM) and calculation abilities remains poorly understood. The present longitudinal study focuses specifically on the role of serial order retention capacities, based on recent findings suggesting a link between ordinal processing in verbal WM and numerical processing tasks. Children were tested when they were in 3rd-year kindergarten (Time 1 [T1]), 1st grade (Time 2 [T2]), and 2nd grade of primary school (Time 3 [T3]), with WM tasks maximizing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 69 publications
12
64
0
Order By: Relevance
“…Their longitudinal study was conducted with young children, and they found a progressive change in the processes underlying ordinal representations. Thus, the strongest conclusion that can be drawn from Attout, Noël, et al (2014) study is that number comparison skills mature earlier than order representations (see also Colomé & Noël, 2012;Lyons et al, 2014).…”
Section: The Current Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Their longitudinal study was conducted with young children, and they found a progressive change in the processes underlying ordinal representations. Thus, the strongest conclusion that can be drawn from Attout, Noël, et al (2014) study is that number comparison skills mature earlier than order representations (see also Colomé & Noël, 2012;Lyons et al, 2014).…”
Section: The Current Studymentioning
confidence: 99%
“…When exploring the relationship between comparison and order processing skills, we did not simply look at correlations between the tasks, but also looked at the relationship between these tasks and arithmetic skills. Although recent studies have very usefully compared the predictive power of numerical comparison and order representations with regard to mathematical/arithmetic skills (Attout, Noël, et al, 2014;Goffin & Ansari, 2016;Lyons et al, 2014;Vogel et al, 2015), the methodologies and participant samples of these studies have left several issues unresolved. Lyons et al (2014) did not explore the relationship between numerical comparison and order processing skills.…”
Section: The Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Although it appears that numerical ordering skills become particularly important from around the age of 6 or 7 (Attout & Majerus, ; Lyons, Price, Vaessen, Blomert, & Ansari, ; Sasanguie & Vos, ), there is also now emerging evidence in support of a role of nonnumerical ordering in mathematical development in the case of younger children (Attout, Noël, & Majerus, ; Morsanyi, van Bers, O'Connor, & McCormack, ; O'Connor, Morsanyi, & McCormack, ). Nonnumerical order processing measures can be broadly divided into two categories: those involving the retrieval of a familiar sequence from long‐term memory, such as the order of familiar daily events, familiar everyday sequences, the months of the year, or letters (Morsanyi, O'Mahony, & McCormack, ; O'Connor et al, ; Sasanguie, De Smedt, & Reynvoet, ; Vos, Sasanguie, Gevers, & Reynvoet, ), and those involving the retrieval of a novel, arbitrary sequence from short‐term memory (order working memory [WM] task; Attout & Majerus, , ; Attout et al, ). O'Connor et al () found that both numerical and nonnumerical ordering measures were related to early mathematical achievement in 4–5‐year‐old children.…”
Section: Table Showing the Results Of Three Longitudinal Studies Regamentioning
confidence: 99%